2019
DOI: 10.1186/s41018-019-0067-6
|View full text |Cite
|
Sign up to set email alerts
|

Identification and prioritization of critical success factors in faith-based and non-faith-based organizations’ humanitarian supply chain

Abstract: In the last few decades, an exponential increase in the number of disasters, and their complexity has been reported, which ultimately put much pressure on relief organizations. These organizations cannot usually respond to the disaster on their own, and therefore, all actors involved in relief efforts should have end-to-end synchronization in order to provide relief effectively and efficiently. Consequently, to smoothen the flow of relief operation, a shared understanding of critical success factors in humanit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…It may be noted that CSFs like donor restrictions, host government policies, limited resources, lack of transport infrastructure, blocked supply lines, custom and clearance issues, limited transport vehicles, workforce shortages, information collection, organization's structure, and culture, and coordination and collaboration are some of the most discussed CSFs in the humanitarian literature. These CSFs are mainly highlighted in last decade by the authors like (Azmat et al 2019a;Dasaklis and Pappis 2018;Yadav and Barve 2018;Bealt et al 2016;Dale and Dulaimi 2016;Ngwenya and Naude 2016;Kabra and Ramesh 2015a;Costa et al 2012;Martinez et al 2011;Balcik et al 2010). However, for this study we will focus mainly on the transport and logistics-related CSFs under discussion in humanitarian literature (Table 2).…”
Section: Humanitarian Relief Operation and Critical Success Factorsmentioning
confidence: 99%
“…It may be noted that CSFs like donor restrictions, host government policies, limited resources, lack of transport infrastructure, blocked supply lines, custom and clearance issues, limited transport vehicles, workforce shortages, information collection, organization's structure, and culture, and coordination and collaboration are some of the most discussed CSFs in the humanitarian literature. These CSFs are mainly highlighted in last decade by the authors like (Azmat et al 2019a;Dasaklis and Pappis 2018;Yadav and Barve 2018;Bealt et al 2016;Dale and Dulaimi 2016;Ngwenya and Naude 2016;Kabra and Ramesh 2015a;Costa et al 2012;Martinez et al 2011;Balcik et al 2010). However, for this study we will focus mainly on the transport and logistics-related CSFs under discussion in humanitarian literature (Table 2).…”
Section: Humanitarian Relief Operation and Critical Success Factorsmentioning
confidence: 99%
“…There are several approaches of SCRM applied to a variety of sectors of the economy in pursue of bettering the risk identification and decision-making process to reduce the vulnerability of a supply chain. However, it should be observed that most studies focus on the response of private companies, while there is also a need to look at the potential of implementing SCRM techniques in organization with less financial and human resources, such as relief organizations that acts on humanitarian purpose (Azmat et al 2019).…”
Section: Supply Chain Risk Management (Scrm)mentioning
confidence: 99%
“…Relief supplies must flow from donors through the supply chain to the final consumers at the right time, at the right cost, in the right quantities and to the right place. Responding flexibly to humanitarian needs is conditional on political, social, infrastructural and environmental factors in the location of a disaster (Azmat et al, 2019).…”
Section: Humanitarian Supply Chain Performancementioning
confidence: 99%